PENGARUH SERAT SABUT KELAPA TERHADAP KUAT LENTUR BETON DENGAN FAKTOR AIR SEMEN O,5 - Elhusna Elhusna; Fepy Supriani; Agustin Gunawan; Mukhlis Islam (Inersia: Jurnal Teknik Sipil, 2019)
18 slabs of 100x100x500 mm dimension had been tested to find out the influence of coconut fiber as the additive to the flexural strength of concrete. The water ratio of the concrete mix design was 0,5. The percentation of coconut fiber were 1%, 2%, 3%, 4% and 5% of the volume of the specimen. The result showed that the fiber additional to the concrete cause the strength getting higher as the percentation getting bigger. The flexural strength of 5% the fiber was 30% higher than the slab of the concrete without the fiber.